Self-supporting nano-porous III-nitride film as well as preparation method and application thereof

By combining ultraviolet-assisted electrochemical corrosion method and selective electrochemical corrosion method, the three-layer epitaxial structure is porous and peeled off, and a self-supported nanoporous Group III nitride film with a three-dimensional communication pore structure is prepared, which solves the problems of high dislocation density and residual stress in traditional materials and achieves efficient light capture capabilities.

CN119650409APending Publication Date: 2025-03-18NANJING XIAOZHUANG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311183518.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-13
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

Traditional heteroepitaxially grown Group III nitride materials have high dislocation density and residual stress, which limits their use in multiple scenario applications. The porosity and light capture capabilities of existing nanoporous GaN films prepared by electrochemical corrosion methods are limited.

Method used

The combination of ultraviolet-assisted electrochemical corrosion method and selective electrochemical corrosion method is used to pore and peel off the three-layer epitaxial structure with a large doping concentration difference to form a self-supported nanoporous Group III nitride film with a three-dimensional communication pore structure.

Benefits of technology

The preparation of self-supported nanoporous Group III nitride films with wafer level, strong controllability of thickness and good surface continuity is achieved, which significantly improves the capture ability of incident light and reduces the electron and optical scattering effects on the grain boundaries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650409A_ABST
    Figure CN119650409A_ABST
Patent Text Reader

Abstract

The invention discloses a self-supporting nano-porous III-group nitride film and a preparation method and application thereof, and the preparation method comprises the steps: sequentially growing an n-GaN layer, an n +-GaN layer and a u-III-group nitride layer on a substrate, and forming a three-layer epitaxial structure; the n-GaN layer serves as a conductive layer, the u-III group nitride layer serves as a target layer, the u-III group nitride layer is made porous through an ultraviolet light-assisted electrochemical corrosion method, and the porous structure is a three-dimensional communicating hole structure; the n +-GaN layer serves as a corrosion sacrificial layer, the n +-GaN layer is corroded and dissolved through a selective electrochemical corrosion method, the porous III-nitride layer is separated from other epitaxial structures, and the self-supporting nano-porous III-nitride film is obtained; wherein the u-III group nitride layer is an unintentionally doped u-III group nitride epitaxial layer, and the doping concentration of the n-GaN layer is lower than that of the n +-GaN layer. According to the preparation method, the self-supporting nano-porous III-nitride film with the porous structure being the three-dimensional communicated pore structure can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a self-supporting nano porous group III nitride film and a preparation method and application thereof, belonging to the technical field. Background Art

[0002] Group III nitrides have the advantages of direct band gap, large breakdown voltage, high saturated electron drift rate, good thermal stability, and strong radiation resistance. They are key basic materials for preparing wide-spectrum, high-efficiency, and high-power optoelectronic and microelectronic devices, and have broad application prospects and huge market demand. However, the defects and dislocation density of traditional heteroepitaxially grown group III nitride materials are relatively high, which limits their application in multiple scenarios.

[0003] Nanoporous III-group nitrides can achieve low dislocation density and low residual stress at the wafer level. Taking GaN materials as an example, through a simple and economical wet etching method, on the one hand, conventional epitaxial GaN materials can be made porous, and on the other hand, wafer-level nanoporous GaN films can be peeled off from the substrate to prepare self-supporting nanoporous GaN films, which can not only release the internal stress of GaN bulk materials and reduce dislocation density, but also break the limitations of traditional GaN's high mechanical strength and chemical inertness on epitaxial peeling, providing a new strategy for the design, performance improvement and heterogeneous integration of new GaN-based optoelectronic devices, flexible devices, and wearable devices.

[0004] Chinese invention patent 201180007613.2 uses electrochemical etching to etch a porous GaN layer on n-GaN epitaxy and peel the porous GaN layer from the substrate to prepare a self-supporting nanoporous GaN film. Hu T et al., published in Nano Journal, "High-Sensitivity and Fast-Speed ​​UV Photodetectors Based on Asymmetric Nanoporous-GaN / Graphene Vertical Junction" (Hu T, Zhao L, Wang Y, et al. High-Sensitivity and Fast-Speed ​​UV Photodetectors Based on Asymmetric Nanoporous-GaN / Graphene Vertical Junction [J]. ACS Nano, 2023, 17 (9): 8411-8419.) also used a similar method to prepare a self-supporting nanoporous GaN film. The nanoporous GaN prepared by electrochemical etching is a longitudinal nanoporous GaN structure perpendicular to the substrate surface. Not only is the porosity limited by the defect density of the GaN epitaxial surface, but the longitudinal pore wall will increase the electron and optical scattering effects on the grain boundary, and the light capture ability is limited.

[0005] Xiao H et al., published in Materials Letters, 2015, 145 (apr. 15): 304-307, prepared and peeled off the nanoporous GaN layer on the bottom-up u-GaN / n-GaN epitaxial structure by using UV-assisted electrochemical etching to prepare a self-supporting nanoporous GaN film. The UV-assisted electrochemical etching method needs to corrode and dissolve a part of the n-GaN epitaxial structure to achieve the purpose of peeling off the nanoporous GaN film, resulting in poor controllability of the thickness of the prepared self-supporting nanoporous GaN film. In addition, long-term high-voltage UV-assisted electrochemical etching is not conducive to obtaining a complete large-area nanoporous GaN film.

[0006] Therefore, the present application proposes a self-supporting nanoporous Group III nitride film and a preparation method and application thereof. Summary of the invention

[0007] The purpose of the present invention is to overcome the deficiencies in the prior art and provide a self-supporting nanoporous group III nitride film and a preparation method and application thereof. The present invention can obtain a self-supporting nanoporous group III nitride film having a porous structure as a three-dimensional interconnected pore structure.

[0008] To achieve the above object, the present invention is implemented by adopting the following technical solutions:

[0009] In one aspect, the present invention provides a method for preparing a self-supporting nanoporous group III nitride film, comprising the following steps:

[0010] The n-GaN layer, n-GaN layer and n-GaN layer are grown on the substrate in sequence. + -GaN layer, u-III group nitride layer, forming a three-layer epitaxial structure;

[0011] Using the n-GaN layer as the conductive layer and the u-III group nitride layer as the target layer, the u-III group nitride layer is made porous by using an ultraviolet light-assisted electrochemical etching method, and the porous structure is a three-dimensional interconnected pore structure;

[0012] n + -GaN layer is a sacrificial layer, and selective electrochemical etching is used to corrode and dissolve n + -GaN layer, so that the porous III-nitride layer is separated from other epitaxial structures to obtain a self-supporting nanoporous III-nitride film;

[0013] The u-III nitride layer is an unintentionally doped u-III nitride epitaxial layer, and the doping concentration of the n-GaN layer is lower than that of the n-GaN layer. + - Doping concentration of the GaN layer.

[0014] Furthermore, the thickness of the n-GaN layer is greater than + -Thickness of the GaN layer;

[0015] Furthermore, the thickness of the u-III group nitride layer is greater than n + -Thickness of the GaN layer;

[0016] Furthermore, the thickness of the self-supporting nanoporous III-nitride film is equal to the thickness of the u-III-nitride layer.

[0017] Furthermore, the doping concentration of the n-GaN layer is 1 to 3e 18 cm -3 ;

[0018] Furthermore, the thickness of the n-GaN layer is 0.5 to 3 μm;

[0019] Furthermore, the n + -The doping concentration of the GaN layer is 3 to 5e 19 cm -3 ,

[0020] Furthermore, the n + -The thickness of the GaN layer is 5 to 50 nm.

[0021] Further, the u-III group nitride layer is an unintentionally doped GaN, AlGaN, InGaN or AlInGaN layer;

[0022] Furthermore, the thickness of the u-III group nitride layer is 10 to 1000 nm.

[0023] Further, the porosity of the self-supporting nanoporous group III nitride film is 5 to 30%;

[0024] Furthermore, the surface roughness of the self-supporting nanoporous group III nitride film is 1.125 to 7.455 nm.

[0025] Furthermore, in the ultraviolet-assisted electrochemical corrosion method:

[0026] The electrolyte is HNO with a concentration of 0.2-2.0 mol / L 3 Solution, H 3 PO 4 Solution, H 2 SO 4solution, NaOH solution, KOH solution, NaNO 3 Solution, Na 2 SO 4 Solution or NaCl solution;

[0027] Further, the UV irradiation power is 200 to 1000W;

[0028] Further, the corrosion voltage is a constant voltage of 2 to 10 V;

[0029] Furthermore, the corrosion time is 0.2 to 5 minutes.

[0030] Furthermore, in the selective electrochemical corrosion method:

[0031] The electrolyte is HNO with a concentration of 0.2-2.0 mol / L 3 Solution, H 3 PO 4 Solution, H 2 SO 4 solution, NaOH solution, KOH solution, NaNO 3 Solution, Na 2 SO 4 Solution or NaCl solution;

[0032] Further, the corrosion voltage is a constant voltage of 20 to 60 V;

[0033] Furthermore, the corrosion time is 0.5 to 2 hours.

[0034] Furthermore, before making the u-III group nitride layer porous by using ultraviolet light-assisted electrochemical etching, the following steps are included:

[0035] Using photolithography technology to form a patterned photoresist on the surface of the three-layer epitaxial structure;

[0036] The three-layer epitaxial structure without photoresist coverage is etched by inductively coupled plasma etching technology, so that the n-GaN conductive layer of the three-layer epitaxial structure without photoresist coverage is exposed and the n-GaN conductive layer of the three-layer epitaxial structure with photoresist coverage is exposed. + -The edge of the GaN layer is exposed, forming an etched groove.

[0037] Further, the self-supporting nanoporous group III nitride film is a self-supporting nanoporous group III nitride single crystal film;

[0038] On the other hand, the present invention provides a self-supporting nanoporous group III nitride film, wherein the self-supporting nanoporous group III nitride film is prepared by the above-mentioned preparation method.

[0039] On the other hand, the present invention provides a self-supporting nanoporous Group III nitride film obtained according to the above-mentioned preparation method or the application of the above-mentioned self-supporting nanoporous Group III nitride film in photocatalytic devices, optoelectronic devices, flexible devices, wearable devices and heterogeneous integration.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] The present invention uses a combination of ultraviolet light-assisted electrochemical etching and selective electrochemical etching to make a three-layer epitaxial structure with a large difference in doping concentration porous and peel off, so as to form a self-supporting nanoporous III-nitride film at the wafer level with strong thickness controllability and good surface continuity, and the self-supporting nanoporous III-nitride film exists in the form of a single crystal.

[0042] The self-supporting nanoporous III-nitride film obtained by the present invention has the characteristics of three-dimensional interconnected pores, which can greatly reduce the electronic and optical scattering effects on the grain boundaries and can greatly improve the ability to capture incident light. It is of great significance in the device design, performance improvement and heterogeneous integration of III-nitride optoelectronic devices, flexible devices, wearable devices, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0043] Figure 1 Shown is a flow chart of an embodiment of a method for preparing a self-supporting nanoporous group III nitride film of the present invention;

[0044] Figure 2 Shown is a SEM image of an embodiment of the porous III-nitride layer 41 and other epitaxial structures of the present invention;

[0045] Figure 3 The figure shows an SEM image of an embodiment of the porous III-nitride layer 41 of the present invention separated from other epitaxial structures;

[0046] Figure 4 Shown is the reflectivity of an embodiment of the self-supporting nanoporous III-nitride film of the present invention (the thickness of the three films is 600 nm);

[0047] Figure 5 The graph is a photocurrent-voltage curve of an embodiment of a photocatalytic experiment of a self-supporting nanoporous GaN film obtained by the preparation method of the present invention;

[0048] In the figure: 10 is a substrate, 20 is an n-GaN layer, 30 is an n + -GaN layer, 40 is a u-III group nitride layer, 21 is an n-GaN conductive layer of a three-layer epitaxial structure without photoresist coverage, 31 is an n-GaN conductive layer of a three-layer epitaxial structure with photoresist coverage +-The edge of the GaN layer, 41 is a porous III-nitride layer, and 41' is a self-supporting nanoporous III-nitride film. DETAILED DESCRIPTION

[0049] The present invention will be further described below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and cannot be used to limit the protection scope of the present invention.

[0050] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", and the like are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Thus, features defined as "first", "second", and the like may explicitly or implicitly include one or more of the features. In the description of the present invention, unless otherwise specified, "multiple" means two or more.

[0051] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal communication of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood by specific circumstances.

[0052] Example 1

[0053] This embodiment introduces a method for preparing a self-supporting nanoporous group III nitride film.

[0054] The preparation method of this embodiment comprises the following steps:

[0055] The n-GaN layer 20, n-GaN layer 21 and n-GaN layer 22 are sequentially grown on the substrate 10. + -GaN layer 30, u-III group nitride layer 40, forming a three-layer epitaxial structure;

[0056] The n-GaN layer 20 is used as the conductive layer and the u-III group nitride layer 40 is used as the target layer. The u-III group nitride layer 40 is made porous by using an ultraviolet-assisted electrochemical etching method. The porous structure is a three-dimensional interconnected pore structure. Figure 2 ;

[0057] n + -GaN layer 30 is a sacrificial layer for etching, and the n-GaN layer is etched and dissolved by selective electrochemical etching. + -GaN layer 30, so that the porous III-nitride layer 41 is separated from other epitaxial structures, and a self-supporting nanoporous III-nitride film 41' is obtained, referring to Figure 3 .

[0058] The u-III group nitride layer 40 is an unintentionally doped u-III group nitride epitaxial layer, and the doping concentration of the n-GaN layer 20 is lower than that of the n-GaN layer 20. + - doping concentration of the GaN layer 30 .

[0059] The ultraviolet light-assisted electrochemical corrosion method is that when ultraviolet light is irradiated to the surface of the u-III nitride layer 40, electron-hole pairs are excited, and these electron-hole pairs are quickly separated through the excitation of a constant voltage power supply, prompting the holes to participate in the oxidation of the III nitride at the anode, so that the unintentionally doped u-III nitride layer can form a porous III nitride layer 41 with a three-dimensional interconnected pore structure in a relatively short time, which has a larger specific surface area and nanoscale confinement effect.

[0060] When applied, in the ultraviolet-assisted electrochemical corrosion method, the lifetime of photogenerated carriers can be extended by delaying the electron-hole recombination process, significantly improving the detector's responsiveness and internal gain.

[0061] The selective electrochemical etching method uses a highly conductive selective wet etching method to precisely etch and dissolve the highly doped n-doped nanostructures from the three-layer epitaxial structure. + The GaN layer 30 and the unintentionally doped porous group III nitride layer 41 will not be corroded, which has the advantage of quickly and widely stripping the porous group III nitride layer 41 of target thickness.

[0062] The porous group III nitride layer 41 is stripped by selective electrochemical etching to obtain a self-supporting nanoporous group III nitride film 41'. Figure 2 The self-supporting nanoporous III-nitride film 41' has low surface roughness and is suitable for heterogeneous integration.

[0063] The present invention first prepares a porous III-nitride layer 41 of target thickness by ultraviolet-assisted electrochemical etching, then removes the ultraviolet irradiation, and directly performs selective electrochemical etching in the same dual-electrode device without transferring the epitaxial structure, so that the nanostructured ... + -GaN layer, the operation process is simple and can effectively improve work efficiency.

[0064] The present invention uses a combination of ultraviolet light-assisted electrochemical etching and selective electrochemical etching to make a three-layer epitaxial structure with a large difference in doping concentration porous and peel off, so as to form a self-supporting nanoporous III-nitride film at the wafer level with strong thickness controllability and good surface continuity, and the self-supporting nanoporous III-nitride film exists in the form of a single crystal.

[0065] The self-supporting nanoporous III-nitride film obtained by the present invention has the characteristics of three-dimensional connected pores, which greatly improves the specific surface area and can effectively increase the photochemical water splitting reaction area of ​​the photoelectrode. The smaller pore spacing enables the photogenerated carriers inside the pore wall to be efficiently separated and the migration distance to the semiconductor / solution interface is reduced, so as to inhibit the recombination of photogenerated carriers during transmission and increase the photocurrent density. It can greatly reduce the electron and optical scattering effects on the grain boundaries and greatly improve the ability to capture incident light. It is of great significance in the device design, performance improvement and heterogeneous integration of III-nitride optoelectronic devices, flexible devices, wearable devices, etc.

[0066] In addition, the present invention can achieve thickness control of the self-supporting nanoporous III-nitride film, which has important experimental research and industrial application significance for the regulation of dynamic processes such as generation, separation, and recombination of carriers inside semiconductor heterojunctions related to the thickness of the self-supporting nanoporous III-nitride film.

[0067] Example 2

[0068] Based on Example 1, this example introduces in detail a method for preparing a self-supporting nanoporous Group III nitride film.

[0069] The preparation method of this embodiment comprises the following steps:

[0070] Step a: sequentially growing n-GaN layers 20, n-GaN layers 21, and n-GaN layers 22 on a substrate 10. + -GaN layer 30, u-III group nitride layer 40, constitute the bottom-up n-GaN / n + -GaN / u-III nitride three-layer epitaxial structure.

[0071] The thickness of the n-GaN layer 20 is greater than that of the n-GaN layer 20. + -GaN layer 30 thickness; u-III group nitride layer 40 thickness is greater than n + -Thickness of the GaN layer.

[0072] In applications, bottom-up n-GaN / n + -GaN / u-III group nitride three-layer epitaxial structure can be grown on a sapphire substrate with a buffer layer by metal organic vapor deposition technology.

[0073] In practical applications, the n-GaN layer 20 is an n-type low-doped conductive layer, and the doping concentration of the n-GaN layer 20 is 1 to 3e 18 cm -3 ; The thickness of the n-GaN layer 20 is 0.5 to 3 μm.

[0074] n + -GaN layer 30 is an n-type highly doped corrosion sacrificial layer. + - The doping concentration of the GaN layer 30 is 3 to 5e 19 cm -3 ;n + The thickness of the GaN layer 30 is 5 to 50 nm.

[0075] The u-III group nitride layer 40 is an unintentionally doped target layer. The u-III group nitride layer 40 is an unintentionally doped GaN, AlGaN, InGaN or AlInGaN layer. The thickness of the u-III group nitride layer 40 is 10 to 1000 nm.

[0076] Step b: using photolithography technology to form a patterned photoresist on the surface of the three-layer epitaxial structure.

[0077] The photolithography technology is a conventional technology in the art, including coating, pre-baking, exposure and development, and the photoresist is a positive photoresist.

[0078] The photoresist pattern forms an electrode window pattern on one side of the upper surface of the three-layer epitaxial structure, and at the same time forms a periodic groove pattern in the area outside the electrode window. The groove pattern is in the shape of a long strip and is perpendicular to the electrode window pattern area.

[0079] Step c: Etching the three-layer epitaxial structure without photoresist coverage by inductively coupled plasma etching technology, so that the n-GaN conductive layer 21 of the three-layer epitaxial structure without photoresist coverage is exposed as an electrode table, so that the n-GaN conductive layer 21 of the three-layer epitaxial structure with photoresist coverage is exposed as an electrode table. + The edge 31 of the GaN layer is exposed, forming an etched groove.

[0080] The bottom of the etching groove is the exposed n-GaN conductive layer, and the sidewall of the etching groove includes n + -The exposed edge of the GaN layer.

[0081] When used, the thickness of the electrode mesa is less than or equal to the thickness of the n-GaN conductive layer 20 .

[0082] In practical applications, the thickness of the electrode table is 20 to 1100 nm.

[0083] Step d: Using the n-GaN layer 20 as the conductive layer and the u-III group nitride layer 40 as the target layer, the u-III group nitride layer 40 is made porous by ultraviolet light-assisted electrochemical etching, and the porous structure is a three-dimensional interconnected pore structure.

[0084] When used, the three-layer epitaxial structure with corrosion grooves is used as the anode for ultraviolet-assisted electrochemical corrosion, which starts from the surface of the u-III group nitride layer 40 and diffuses inward to form a three-dimensionally connected nanoporous III group nitride layer.

[0085] In a double-electrode electrolytic cell at room temperature, a metal platinum electrode is used to clamp the electrode table of the n-GaN conductive layer, another metal platinum electrode is used as a counter electrode, and HNO with a concentration of 0.2 to 2.0 mol / L is used. 3 Solution, H 3 PO 4 Solution, H 2 SO 4 solution, NaOH solution, KOH solution, NaNO 3 Solution, Na 2 SO 4 Solution or NaCl solution is used as the electrolyte, and under the conditions of vertically incident ultraviolet light irradiation power of 200 to 1000W and corrosion voltage of 2 to 10V constant voltage, ultraviolet light-assisted electrochemical corrosion is started from the surface of the u-III group nitride layer 40 and diffuses inward to make the u-III group nitride layer 40 porous to form a porous group III nitride layer 41; the ultraviolet light-assisted electrochemical corrosion time is 0.2 to 5 minutes; during the corrosion process, in order to keep the electrolyte uniform, the electrolyte needs to be stirred at a uniform speed by a magnetic stirrer.

[0086] In practical applications, the porosity of the porous III-nitride layer 41 is not limited by the density of defects on the nitride epitaxial surface, has great adjustability, and avoids the electron and optical scattering effects caused by the longitudinal pore walls, so that the light capture ability of the porous III-nitride layer 41 is greatly improved. Figure 4 .

[0087] In optoelectronic applications, the light extraction efficiency of a material can be judged based on the reflectance spectrum. The lower the reflectivity, the higher the material's efficiency in extracting light in the corresponding band. In this way, the interaction between the material and the light in the corresponding band is stronger, and the photoelectric efficiency is higher.

[0088] Those skilled in the art can adjust the porosity and surface roughness of the porous Group III nitride layer 41 by collaboratively regulating the UV irradiation power, etching time and etching voltage in the UV-assisted electrochemical etching method.

[0089] Step e: Take n+ -GaN layer 30 is a sacrificial layer for etching, and the n-GaN layer is etched and dissolved by selective electrochemical etching. + The -GaN layer 30 separates the porous group III nitride layer 41 from other epitaxial structures to obtain a self-supporting nanoporous group III nitride thin film 41'.

[0090] When used, the three-layer epitaxial structure with the porous group III nitride layer 41 is used as an anode for selective electrochemical etching, and the high conductivity sensitivity of the electrochemical etching is utilized. The selective electrochemical etching is carried out from the three-layer epitaxial structure with the photoresist covering the n + -GaN layer starts at the edge 31 and advances inward until the n- + The -GaN layer 30 is dissolved, so that the porous group III nitride layer 41 is separated from other epitaxial structures, and a self-supporting nanoporous group III nitride thin film 41' is obtained.

[0091] In a two-electrode electrolytic cell at room temperature, a metal platinum electrode is used to clamp the electrode table, and another metal platinum electrode is used as a counter electrode. 3 Solution, H 3 PO 4 Solution, H 2 SO 4 solution, NaOH solution, KOH solution, NaNO 3 Solution, Na 2 SO 4 solution or NaCl solution as the electrolyte, under the condition of constant voltage of 20 to 60 V, the n-type three-layer epitaxial structure covered with photoresist is + -GaN layer starts at the edge 31 and advances inward until the n- + After the -GaN layer 30 is dissolved and the porous group III nitride layer 41 is separated from other epitaxial structures, the selective electrochemical corrosion is stopped; during the corrosion process, in order to keep the electrolyte uniform, the electrolyte needs to be stirred at a uniform speed by a magnetic stirrer.

[0092] The thickness of the self-supporting nanoporous III-group nitride film 41' is equal to the thickness of the u-III-group nitride layer 40. Figure 3 The porosity of the self-supporting nanoporous III-nitride film 41' is 5 to 30%; the surface roughness of the self-supporting nanoporous III-nitride film 41' is 1.125 to 7.455 nm.

[0093] In addition, the UV-assisted electrochemical etching method will not affect the long-range order characteristics of the single crystal u-III group nitride layer 40. The porous III group nitride layer 41 obtained after UV-assisted electrochemical etching is still a single crystal. Therefore, the self-supporting nanoporous III group nitride film 41' is a self-supporting nanoporous III group nitride single crystal film.

[0094] The self-supporting nanoporous group III nitride thin film 41 ′ is a self-supporting nanoporous group III nitride thin film 41 ′ at a wafer level of 2 inches or more.

[0095] Example 3-15

[0096] Based on Example 1 or 2, 13 groups of embodiments are set up. The parameter settings of the three-layer epitaxial structure in each group of embodiments are detailed in Table 1. The parameter settings of the ultraviolet-assisted electrochemical corrosion method and the selective electrochemical corrosion method in each group of embodiments are detailed in Table 2. The parameters of the self-supporting nanoporous Group III nitride film 41' obtained in each group of embodiments are detailed in Table 3.

[0097] Table 1 Parameters of three-layer epitaxial structure

[0098]

[0099] Table 2 Parameters of UV-assisted electrochemical etching and selective electrochemical etching

[0100]

[0101] Table 3 Parameters of self-supporting nanoporous III-nitride films

[0102]

[0103] Among them, in Examples 3-12, the self-supporting nanoporous Group III nitride film obtained is a self-supporting nanoporous GaN film, in Example 13, the self-supporting nanoporous Group III nitride film obtained is a self-supporting nanoporous AlGaN film, in Example 14, the self-supporting nanoporous Group III nitride film obtained is a self-supporting nanoporous InGaN film, and in Example 15, the self-supporting nanoporous Group III nitride film obtained is a self-supporting nanoporous AlInGaN film.

[0104] Compared with the existing self-supporting planar GaN film and self-supporting longitudinal porous GaN film, the photogenerated current of the self-supporting nanoporous GaN film obtained in this application is increased by 3.09 times and 1.96 times, respectively. Figure 5 .

[0105] The present invention grows a three-layer epitaxial structure with a large difference in doping concentration from bottom to top on a substrate, takes an n-GaN layer as a conductive layer, and uses an ultraviolet-assisted electrochemical etching method to etch the unintentionally doped u-III group nitride layer into a porous III group nitride layer in a short time, and combines a high-conductivity selective electrochemical etching method to accurately dissolve n + -GaN layer, which has the advantage of rapid and large-area preparation of self-supporting nanoporous III-nitride films of target thickness.

[0106] The present invention can achieve thickness control of self-supporting nanoporous III-nitride thin films, which has important experimental exploration and industrial application significance for the regulation of dynamic processes such as generation, separation, and recombination of carriers inside semiconductor heterojunctions related to the thickness of self-supporting nanoporous III-nitride thin films.

[0107] Example 16

[0108] This example introduces in detail a self-supporting nanoporous group III nitride film, which is prepared according to the preparation method described in Example 1 or 2.

[0109] Embodiment 17

[0110] This embodiment introduces in detail the application of the self-supporting nanoporous Group III nitride film prepared by the preparation method described in Example 1 or 2 or the self-supporting nanoporous Group III nitride film described in Examples 3-15 in photocatalysis, optoelectronic devices, flexible devices, wearable devices and heterogeneous integration.

[0111] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the technical principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a self-supporting nanoporous group III nitride film, characterized in that: The steps include: An n-GaN layer (20), an n-GaN layer (20) and a n-GaN layer (20) are sequentially grown on a substrate (10). + -GaN layer (30), u-III group nitride layer (40), forming a three-layer epitaxial structure; The n-GaN layer (20) is used as a conductive layer and the u-III group nitride layer (40) is used as a target layer, and the u-III group nitride layer (40) is made porous by using an ultraviolet light-assisted electrochemical etching method, wherein the porous structure is a three-dimensional interconnected pore structure; n + The GaN layer (30) is a sacrificial layer for etching, and the n-GaN layer is etched and dissolved by selective electrochemical etching. + -GaN layer (30), so that the porous group III nitride layer (41) is separated from other epitaxial structures to obtain a self-supporting nanoporous group III nitride film (41'); The u-III group nitride layer (40) is an unintentionally doped u-III group nitride epitaxial layer, and the doping concentration of the n-GaN layer (20) is lower than that of the n-GaN layer (20). + - doping concentration of the GaN layer (30).

2. The method for preparing a self-supporting nanoporous group III nitride film according to claim 1, characterized in that: The thickness of the n-GaN layer (20) is greater than + - thickness of the GaN layer (30); And / or, the thickness of the u-III group nitride layer (40) is greater than n + -Thickness of the GaN layer; And / or, the thickness of the self-supporting nanoporous III-nitride film (41') is equal to the thickness of the u-III-nitride layer (40).

3. The method for preparing a self-supporting nanoporous group III nitride film according to claim 1, characterized in that: The doping concentration of the n-GaN layer (20) is 1 to 3e 18 cm -3 ; And / or, the thickness of the n-GaN layer (20) is 0.5 to 3 μm; and / or, the n + - The doping concentration of the GaN layer (30) is 3 to 5e 19 cm -3 , and / or, the n + - The thickness of the GaN layer (30) is 5 to 50 nm. and / or, the u-III group nitride layer (40) is an unintentionally doped GaN, AlGaN, InGaN or AlInGaN layer; And / or, the thickness of the u-III group nitride layer (40) is 10 to 1000 nm.

4. The method for preparing a self-supporting nanoporous group III nitride film according to claim 1, characterized in that: The porosity of the self-supporting nanoporous group III nitride film (41') is 5 to 30%; And / or, the surface roughness of the self-supporting nanoporous group III nitride film (41') is 1.125-7.455 nm.

5. The method for preparing a self-supporting nanoporous group III nitride film according to claim 1, characterized in that: In the ultraviolet-assisted electrochemical corrosion method: The electrolyte is HNO3 solution, H3PO4 solution, H2SO4 solution, NaOH solution, KOH solution, NaNO3 solution, Na2SO4 solution or NaCl solution with a concentration of 0.2 to 2.0 mol / L; and / or, the ultraviolet light irradiation power is 200 to 1000 W; and / or, the corrosion voltage is a constant voltage of 2 to 10 V; And / or, the corrosion time is 0.2 to 5 minutes.

6. The method for preparing a self-supporting nanoporous group III nitride film according to claim 1, characterized in that: In the selective electrochemical corrosion method: The electrolyte is HNO3 solution, H3PO4 solution, H2SO4 solution, NaOH solution, KOH solution, NaNO3 solution, Na2SO4 solution or NaCl solution with a concentration of 0.2 to 2 mol / L; and / or, the corrosion voltage is a constant voltage of 20 to 60 V; And / or, the corrosion time is 0.5 to 2 hours.

7. The method for preparing a self-supporting nanoporous group III nitride film according to claim 1, characterized in that: Before the u-III group nitride layer (40) is made porous by using the ultraviolet light-assisted electrochemical etching method, the following steps are included: Using photolithography technology to form a patterned photoresist on the surface of the three-layer epitaxial structure; The three-layer epitaxial structure not covered by the photoresist is etched by inductively coupled plasma etching technology, so that the n-GaN conductive layer (21) of the three-layer epitaxial structure not covered by the photoresist is exposed, and the n-GaN conductive layer (21) of the three-layer epitaxial structure covered by the photoresist is exposed. + The edge (31) of the GaN layer is exposed, forming an etched groove.

8. The method for preparing a self-supporting nanoporous group III nitride film according to claim 1, characterized in that: The self-supporting nanoporous group III nitride film (41') is a self-supporting nanoporous group III nitride single crystal film.

9. A self-supporting nanoporous group III nitride film, characterized in that: The self-supporting nanoporous group III nitride film is prepared by the preparation method according to any one of claims 1 to 8.

10. Application of the self-supporting nanoporous III-nitride film obtained by the preparation method according to any one of claims 1 to 8 or the self-supporting nanoporous III-nitride film according to claim 9 in photocatalysis, optoelectronic devices, flexible devices, wearable devices and heterogeneous integration.

Citation Information

Patent Citations

  • Conductivity based selective etch for gan devices and applications thereof

    CN102782818A